Predictors of excessive use of social media and excessive online gaming in Czech teenagers - Spilková, Jana; Chomynová, Pavla; Csémy, Ladislav (Journal of behavioral addictions, 2017)
Background and aims Young people's involvement in online gaming and the use of social media are increasing rapidly, resulting in a high number of excessive Internet users in recent years. The objective of this paper is to analyze the situation of excessive Internet use among adolescents in the Czech Republic and to reveal determinants of excessive use of social media and excessive online gaming. Methods Data from secondary school students (N = 4,887) were collected within the 2015 European School Survey Project on Alcohol and Other Drugs. Logistic regression models were constructed to describe the individual and familial discriminative factors and the impact of the health risk behavior of (a) excessive users of social media and (b) excessive players of online games. Results The models confirmed important gender-specific distinctions - while girls are more prone to online communication and social media use, online gaming is far more prevalent among boys. The analysis did not indicate an influence of family composition on both the excessive use of social media and on excessive online gaming, and only marginal effects for the type of school attended. We found a connection between the excessive use of social media and binge drinking and an inverse relation between excessive online gaming and daily smoking. Discussion and conclusion The non-existence of significant associations between family environment and excessive Internet use confirmed the general, widespread of this phenomenon across the social and economic strata of the teenage population, indicating a need for further studies on the topic.
Keywords: internet; kouření; adolescents; social media; videohry; mladiství; Česká republika; sexuální faktory; školy; mužské pohlaví; Internet; Czech Republic; Schools; Smoking; ESPAD; Binge Drinking; Video Games; ženské pohlaví; sociální média; excessive Internet use; Behavior, Addictive; návykové chování; Humans; rodinné vztahy; online gaming; Sex Factors; Social Media; nárazové pití alkoholu; rizikové faktory; Family Relations; Female; Risk Factors; Adolescent; lidé; Male